Legal Rhetoric and Criminal Law - Encalada González, Dennis Valeria (2018)
The following investigation aims to analyze the origin of the relationship between rhetoric and Criminal Law; in fact, the rhetoric or also called “the art of persuasion” where writing is not necessary, was introduced by Socrates, an important Greek philosopher and teacher who lived in Athens in the 300 BC. It is intrinsic to Criminal Law since its normative material is not perfectly codified; in fact, rhetoric constitutes a sort of instrument by which a citizen can support his own opinion both in the political and judicial sphere before, in this case, a criminal trial presenting findings of the fact and an excellent narration in order to obtain the jury’s consent. It is also of great interest to mention the importance of identifying the differences and equations between rhetoric and legal considerations; identify the main reasons why the Criminal Law requires rhetoric and then compare it with the Ecuadorian Criminal Law; examine the strategies used by “the art of persuasion” to prove the benefits and disadvantages it brings in Criminal Law; finally, to present some observations to reduce this problem finding a balance in the practice of rhetoric. KEYWORDS: rhetoric, logic, right, criminal process, rationality. JEL CODE: K14, L10